Contested densification: Sustainability, place and expectations at the urban fringe - Van Neste, Sophie L.; Royer, Jean-Philippe (Frontiers in Sustainable Cities, 2022)
The discourse of sustainability-by-density is dominant in urban policies and climate-friendly urbanism today. Yet, with current failures and disparities in the regulation of dense development and land speculation, the effects of such policies are not exclusively positive. In this article, we address citizen opposition to densification in urban peripheries of the Global North, especially in the North American context, with particular focus on a case at the urban fringe of the Montreal metropolitan area (Canada). We contribute to existing scholarship on a relational approach to urban sustainability with the objective of better understanding the narratives and governance dynamics that unfold in urban peripheries. In the case studied, the gap between residents’ subjective experience of the ongoing transformations and the State discourses at different scales is particularly important, yet little understood after several years of public participatory meetings and two lawsuits. We develop the notion of situated expectations to show how actors entertain different expectations of the performance of State and citizen practices in favour of sustainability, which are grounded in their respective relationships to place, scale and the urban boundary. The lack of circulation and mutual recognition between these expectations makes the construction of coalitions and shared participatory governance practices much more problematic.